Handel’s Pasticci between Music History and Current Music Practice at the Handel Festival in Halle - Birnbaum Clemens (Musicology Today)
Looking back on the first Handel Festival in Halle in 1922, it is argued that a close connection between science and practice has been characteristic of the Halle Festival from the very beginning. Arrangements of Handel’s works were made both by performing musicians and by recognised musicologists. Despite this common editing practice, the opera-pasticcio group of works has been disregarded until the early twenty-first century. Since 2012, the Stiftung Händel-Haus in Halle has been considering a reassessment of this group of works. Alongside performances, editions were to be produced. The positive results of this initiative are listed, but its failures are also pointed out. It is believed that the pasticci and Handel’s composition practice will ultimately only receive a suitable appreciation if a new aesthetic of the music work is applied as a foundation.